New Horizons: Novel Adrenal Regenerative Therapies - Bornstein, Stefan R (J Clin Endocrinol Metab, 2020)
Adrenal insufficiency requires lifelong corticoid replacement therapies. However, current therapies are not able to replace the physiological circadian pattern of the adrenal cortex and are associated with many metabolic, vascular, neuroendocrine, and mental perturbations. Therefore, regenerative and more curative strategies would be desirable. In the current perspective, we describe emerging new regenerative therapies for the treatment of adrenal insufficiency. In particular, we discuss gene therapy and cell replacement strategies. Furthermore, we discuss how adrenal cells might be used as a source for regenerative therapies of nonadrenal neurodegenerative diseases such as Parkinson disease.